Activation and turnover of the plant immune signaling kinase BIK1: a fine balance. Issue 2 (5th August 2022) - Gonçalves Dias, Márcia; Soleimani, Faranak; Monaghan, Jacqueline
Abstract: Mechanisms to sense and respond to pathogens have evolved in all species. The plant immune pathway is initiated by the activation of transmembrane receptor kinases that trigger phosphorylation relays resulting in cellular reprogramming. BOTRYTIS-INDUCED KINASE 1 (BIK1) is a direct substrate of multiple immune receptors in Arabidopsis thaliana and is a central regulator of plant immunity. Here, we review how BIK1 activity and protein stability are regulated by a dynamic interplay between phosphorylation and ubiquitination.